A social history of Japanese Immigration into the Philippines with special reference to Japanese Immigration in Iloilo - Mabunay, Maria Luisa
This study sets out to contribute data and insights toward a deeper understanding of current trends in Phil-Japan relations through an analysis of the patterns of social interaction of first and second generation Japanese immigrants as ethnic categories in the local communities. The study is based on an exposition of the pertinent historical antecedents and characteristics of Japanese settlement in the Philippines, particularly as exemplified in the experience of the province of Iloilo. The basic notion of the study is that, while the course of Japanese immigration into the Philippines has been largely determined by the nature and state of general relations between the Philippines and Japan, the settlements have in turn helped shape the boarder relations between the two countries. Various primary and secondary sources attest to two periods of Japanese settlement in the country: first, during the late sixteenth and early seventeenth centuries, and second, during the late nineteenth and early twentieth centuries. A third period appears to have crystallized in recent decades, closely following the post-World War II departure of Japanese settlers. During these three periods, Japanese movements into and out of the country mirrored qualitative shifts in officials relations between Japan and Philippines. As relations were fostered or restricted by Japanese and Philippine policies, so did the migrants wax or wane. Japanese commercial interest in this area of the Nanyo and the Japanese Christians' search for refuge from domestic religious persecution engendered the first period of Japanese settlement in the Philippines. This era of Japanese residence was chronologically brief and geographically limited to areas in and around Manila. Still, the feudal migratory stream not only linked the twocountries but also looked forward to the second period of Japanese settlement. After a span of about two centuries, commercial and industrial interests of the Meiji rulers, and later the urge for territorial expansion into the Nanyo, induced the second period of Japanese immigration into the Philippines. Active encouragement from the Spanish,American, and Filipino administrators, and the laxity of controls over the provincial activities of Japanese settlers boosted the migrations, so that by 1939 the Japanese residents in the country numbered more than 29,000. In relation to to other foreign minorities in the Philippines and to the total population, this number was not significant, but the settlers nevertheless made their mark in the agricultural, commercial, and fishing sectors. Their success was largely due to their superior technology, capital resources,and the spirited support they got from their government and private industry. The act of migration may be said to have transplanted the Japanese into an unstructured and greatly diminished social sphere which they sought to define and come to terms with during their stay in the Philippines. They may have felt constrained to embrace newvalues and aspirations, to rearrange their social relations with other Japanese migrants, and to widen their contracts with external society. Absorption into the host society, however, proved elusive. The Japanese, who had been drawn to the country by economic motives, found scant immediate profit in assuming roles that did not furthertheir economic aspirations. In addition, Japanese values, institutions, and associations effectively isolated them from the rest of those living in the local communities where the Japanese settlers practiced their chosen trades. This separateness found its most significant expression and source of reinforcement in the Japanese Associations that sprung up in several communities. Established in 1919, the Japanese Association in Iloilo would have served to link the Japanese settlers with the rest of the local population, except that the assiduity with which the Association strove to enhance the economic and and social well-being of its members precluded their integration into Ilonggo society. The Association's ties with the Japanese nation and culture was evidenced by its support of the Iloilo Japanese primary School, which was officially subsidized by the Japanese government through the consulate-General. Aside from the fact that its members shared the common ethnic "attribute" of having Japanese origins in cosmopolitan Iloilo society in the early twentieth century, the Association provided the "frame" within which the members interacted with the rest of society. In this context, it may even be asserted that the Iloilo Japanese Association was a modified ie of the Japanese settler. Its membership and leadership functions were clearly defined, and it evinced the common concerns of its members through its management of their enterprise, the Iloilo Japanese Primary School. The alacrity with which the Japanese migrant in Iloilo learned new skills and adopted coping mechanisms would seem to indicate a break with his traditional status-image and set of values. Yet, his basic motivation usually qualified his adjustment. His "sectors of articulation" were principally trade, fishing, and the skilled occupations, hence, in the choice of the residence, he tended to gravitate to areas where he could pursue his livelihood. Japanese nationalistic fervor for a New Order in Asia in the late 1930's rested on the belief in Japanese superiority. Its military expression made inconceivable the settlers' integration into Philippine society. The Japanese in the Philippines who took part in their country's war efforts, were defeated by the Allies and later repatriated. The first two periods of Japanese settlement in the Philippines were punctuated respectively by the Tokugawa policy of seclusion in the mid-seventeenth century and Japan's defeat in world War in the mid-twentieth century. In both instances, while Japanese immigration ostensibly ended, Japanese individuals and families of Japanese ancestry remained in the country. Their continued presence after the second period, added to the relatively short period of time between the disruption and restoration of Philippines-Japan relations after World War II, as well as the recent resurgence of Japanese economic expansion into Southeast Asia, could well result in the revitalization of Japanese settlements in the Philippines. Moreover, since the normalization of relations between Japan and the Philippines in 1956, Japanese nationals have come into the country for transient as well as more permanent purposes. Among the post-war Japanese residents are the Japanese wives of filipinos once employed at Okinawa and a number of "Japanese-Filipinos".But while the pre-war Japanese in the Philippines, in general, and in Iloilo in particular, consistently maintained and cultivated aspects of their original culture, the present group of Japanese residents betray a relatively low awareness of ethnicity. This is due chiefly to their geographic and social dispersal through-out the Philippines following the post-war repatriations of Japanese nationals and the tendency of those left behind to downplay their identification with the Japanese, for fear of social ostracism. These individuals meet together infrequently and only at the instance of such Japan-based associations of former Japanese civilians and soldiers in Iloilo.